Pica and amylophagy are common among Malagasy men, women and children. - Christopher D Golden (Public Library of Science (PLoS), 2012)
Pica, the craving and purposive consumption of non-food substances, is of public health concern for its potential deleterious and salubrious health consequences. However, neither its prevalence nor demographic correlates have been well characterized. Therefore, we conducted the first population-based study of pica and amylophagy in Madagascar. From February to December 2009, we surveyed pica and amylophagy behaviors in a random sample of 760 individuals >5 years in 167 households among two ethnic groups in 16 villages in the Makira Protected Area of Madagascar. Of the 760 individuals interviewed, 62.5% were children (5-11 years), 5.4% were adolescents (12-16 years), and 35.1% were adults (≥ 17 years). Thirteen non-food items were reported being consumed. Across the entire population in the prior year, the prevalence of geophagy was 53.4%, of amylophagy, 85.2%, and of other pica substances (e.g. charcoal, chalk) was 19.0%. The prevalence of these behaviors was not higher during pregnancy. These findings differ from previous studies in terms of the higher overall prevalence of these behaviors, the high prevalence among men, and the absence of any peak in behaviors during pregnancy. However, there are two categories of substances that elevate our estimates but fall outside the strict definition of pica as a craving: 1) substances consumed for self-medication and 2) substances viewed as food, such as all amylophagic substances in this case. Our results suggest that population-based studies of pica should include males of all ages. Further, the prevalence of the behavior underscores the importance of understanding the etiology and health consequences of these ingestive behaviors (Abstract S1).